Moral thinkings - "Hare, R.M." (Oxford, 1981)
By distinguishing between two different levels of moral thinking, we see how utilitarian reasoning at the critical level$1 (Benlisting the impartial sympathy for others$1 (Bpredicaments, which we must have if we fully understand them and universalize our preferences as morality requires$1 (Bgenerates moral principles for use at the intuitive level, which square with common intuitions, e.g. about justice and rights. The reasoning itself depends on the logic of concepts, which all who ask moral questions are already using.s
Keywords: Ethics